Digital Transaction: A Catalyst for Financial Inclusion and Job Creation - Maigari, Muhammad Abdullahi; Yelwa, Mohammed Muson (Journal of Digital Marketing and Halal Industry, 2023)
What informed the rationale for developing this topic was the growing number of Point of Sale (POS) Agents in Katsina Metropolis and their clients/customers. The central focus of this article is to examine the role of Agent Banking which is part of financial inclusion in poverty reduction in Katsina metropolis. The researchers adopted a survey research design where data were elicited using quantitative research techniques from the targeted respondents. The data collected were analyzed and presented which revealed that there are at least twenty Post of Sale (POS) outlets located in each major street of Katsina Metropolis. The study also found that the POS has become a veritable source of livelihood for those who are into Agency Banking in the area. Additionally, the availability of POS Agents has influenced a significant population of the metropolis to adopt the use of digital systems of payment in their businesses and other financial transactions. It has revealed that the cashless policy has facilitated or accelerated the growth of digital marketing in the Katsina metropolis, entrepreneurs in the area are now selling their wares online and receiving payment via the same system which has eliminated the barriers created by time and space. The theoretical implication of the cashless policy was the unintended consequences it generated. It is referred to as the Cobra Effect during the 2033 Generation Elections in Nigeria. The decision to redesign the currency and reduce the amount of money in circulation has created more demands for cash hence luring some voters to exchange their votes for cash on election day. The practical implications of the findings of this study are twofold: The cashless policy has encouraged some of the people who are financially excluded were able to open bank accounts. It has enabled marketers to carry out financial transactions online without physical contact between the buyer and seller with the aid of electronic money payment systems.